Mediatization of the image of African-American women as protagonists: Experience of Interaction of Brazilian women with Contraintuitive Advertisements - Leite, Francisco (Cuestiones de Género: de la igualdad y la diferencia, 2017)
This paper presents an explanation proposal about the meaning links that are produced when there is interaction of Brazilian women with counterintuitive advertisements, which show Afro-American women as protagonists of their discourses. It is a qualitative investigation oriented by the theoretical interconnection of perspectives of Symbolic Interactionism and Mediatization Studies focused on influences of the media in the (re)elaboration of social identities, as basilar theoretical referential, and through the Constructivist Grounded Theory, as a methodological approach. The results of this research enabled the articulation of the representative theoretical model “Interaction experiences of brazilian women with counterintuitive advertisements”, from which this paper presents the category "The image of the Afro-American woman in complex creations and extreme representations".